Scenografie dell'immaginario narrato: i mondi alla rovescia e i paesi di cuccagna - Chiara Lepri (Firenze University Press, 2018)
The paper deepens the literary motif of the upside down world and the land of Cockaigne as a fantastic-conceptual paradigm, which is, through wonderful and evocative scenarios, the background, not only to many fairy tales, with which it is intimately linked, but also to numerous narratives for today's childhood between persistences and distortions, demonstrating utopian and even subversive tension that is one of the distinctive feature of children's literature itself.